Islam and the Struggle for Religious Pluralism in Indonesia: A Political Reading of the Religious Thought of Mukti Ali - Munhanif, Ali (Studia Islamika, 1996)
Problems of inter-religious dialogue is one of the important discourse in the development of religious thought in modern Indonesia. One of the leading Muslim intellectuals seoran put a great interest in the discourse of religious thought is Prof. HA Mukti Ali, former Minister of Religious Affairs of the Republic of Indonesia, which has served as Rector of IAIN Yogyakarta.In the view of many people, known as Mukti Ali Muslim leaders who have diverse Islamic thought. He, set in the traditional students and the cast of revivalist organization, Muhammadiyah is the pioneer of Comparative Studies of Religion in Indonesia. He is also known as the man who chose the problem of inter-religious dialogue in Indonesia as 'immortal work' throughout his life. Equally important, Mukti Ali is an Indonesian Religious Affairs Minister re-orientation is important in the political-religious wisdom in the New Order.DOI: 10.15408/sdi.v3i1.814